The importance of curettage in cases of sexual violence - Osman Celbis; Turgay Bork; Abdullah Karaer; Ozlem Ozel Ozcanli; Esra Porgali Zayman (Medicine Science, 2017)
Sexual assault is among the gravest crime against the physical and moral integrity of an individual. When sexual assault results in pregnancy it causes further psychological and social damage. This study aims to examine the reasons for delayed reporting in cases of sexual assault that result in pregnancy, and the importance of abortion in such cases. Seven cases referred by the judicial authorities to Inonu Universitys Turgut Ozal Medical Center for uterine evacuation are included in the study. The cases were examined in terms of age, whether the parents were still alive, place of residence, assaulter characteristics, mental levels of victims, psychiatric examination results, and gestational week upon referral to the hospital. The mean age of the cases was 17.42±2.76 years. Six of the cases were referred from Malatya and one was referred from a neighboring province. Four of the cases were past their 10th gestational week. Abortions were performed in six of the cases. One of the women, in the 19th week of pregnancy, decided not to have the abortion upon consultation with her family. The women in the cases were, on average, 76 days pregnant upon referral to the center. Their medical histories indicated that five of the cases hid their pregnancy because they were concerned about their familys reaction. None of the cases knew that they were able to end the pregnancy until week 20. Pregnancy is one of the unwanted and preventable consequences of sexual assault. The familys attitude toward the victim plays an important role in earlier detection of the cases. In addition to legislation concerning ending pregnancies, victims and families should be informed about this topic to prevent further trauma for the victim and the to be born child. [Med-Science 2017; 6(4.000): 743-745]